Candidates for Bariatric Surgery: Morbidly Obese Patients with Pulmonary Dysfunction - Yu-Feng Wei; Huey-Dong Wu (Hindawi Limited, 2012)
Obesity is a well-known major risk factor of cardiovascular disease and is associated with various comorbidities. The impact of obesity on pulmonary function remains unclear. Reductions in chest wall compliance and respiratory muscle strength due to a high percent body fat and localized fat distribution contributes to impaired pulmonary function and the occurrence of adverse respiratory symptoms. Dietary modifications and pharmaceutical agents are not effective in the long-term treatment of obesity. Treatment of morbidly obese patients using bariatric surgery has increased each year, especially after the introduction of video laparoscopic techniques. Effective weight loss after bariatric surgery may improve cardiovascular disease risk factors, including diabetes, hypertension, dyslipidemia, atherosclerosis, inflammation, chronic kidney disease, obstructive sleep apnea, and obesity hypoventilation syndrome. Bariatric surgery has also been associated with significantly improved respiratory symptoms and pulmonary function. We currently present a review of principal studies that evaluated the effects of obesity on pulmonary function and the identification of anthropometric factors of obesity that correspond to the reversal of respiratory symptoms and impaired pulmonary function after bariatric surgery.